Low energy production impact on lean flow. Issue 3 (7th April 2015) - Ball, Peter
Abstract : Purpose: – Rising energy costs and potential scarcity are driving energy reduction initiatives in manufacturing companies. The reduction in energy use is complementary to the classic lean production philosophy and the lean and green literature implies that reducing energy waste supports lean objectives. The purpose of this paper is to examine this perceived positive correlation and identify the impact level of energy reduction of lean product flow. Design/methodology/approach: – To achieve this, published case studies and practices from interview were gathered and categorised against a waste management hierarchy. Findings: – Energy reduction activities implicitly reduce waste which is compatible with the lean waste objective, however, when applying the waste hierarchy principle to energy efficiency practice, lean product flow is progressively constrained or compromised towards the lower levels of the hierarchy. Research limitations/implications: – The hierarchical classification seeks to communicate how reported energy efficiency improvements will/will not impact on flow. The research focuses on the modification of existing discrete part production facilities towards greater energy efficiency and neglects alternative production technologies and new build. The results suggest that as manufacturers seeking to be more energy efficient move away from preventative actions to more reduce and reuse actions then production flexibility could become restricted and the design of production facilities make re-think the fast, linear and short flow of product. Practical implications: – Examples of industrial practices are provided to show the implications of energy reduction practice on production flow. Originality/value: – Categorises the relationship between classic lean and industrial low-energy initiatives to provide insight to how higher energy cost could impact on production.